Bio-inspired algorithms for cloud computing: a review. (2015) - Balusamy, Balamurugan; Sridhar, Jayashree; Dhamodaran, Divya; Krishna, P. Venkata
Cloud computing provides internet-based services to access different kind of service or resources, eliminating the need for centralised data access. There are several challenges available in cloud computing, where specific issues like resource provisioning, load imbalance and performance improvement can be solved using bio-inspired algorithms. Bio-inspired algorithms have the tendency to solve various kinds of problems naturally by providing optimised solutions. Though it is not used in cloud computing to a greater extent, it is applicable in networking, pattern recognition, data mining, wireless sensor networks, etc. The adaptability influences the use of bio-inspired algorithms to solve the major issues in cloud computing. The paper provides an extensive survey of bio-inspired algorithms for solving and optimising problems related to resource scheduling, load balancing, file searching and security in cloud computing. The work compares the performance, response time and cost optimisation of each algorithm applicable for cloud computing environment.